PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KEMAMPUAM PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 1 RANAH PESISIR - Rismaini, Lili; Roza, Melia (STKIP Pesisir Selatan, 2019)
Mathematics learning outcomes obtained by students of SMP 1 in the Coastal Zone are still low. This happens because the learning process is still teacher-centered. In addition, the lack of mastery of prerequisite material is also one of the obstacles that influence the low student learning outcomes. One effort that can be done to overcome is to use the Think Pair Share learning model. This study aims to determine the effect of Think Pair Share learning model on students' mathematical problem solving abilities. The study was conducted in two classes grouped as experimental class and control class. The learning experimental class is done using the Think Pair Share learning model, while the Control learning class is done using the Conventional Model. The research data was obtained from the results of learning tests which data analysis was carried out using the t test. The results of data analysis show that students' mathematical problem solving abilities using learning Think Pair Share learning models are better than students who learn using conventional models